Elbow dislocation accompanied by ulnar coronoid process and radial head fractures: A report of a terrible triad injury in a child - Amir Bisadi; Fatemeh Abbasi; Mohammad Abbasalizadeh; Mahdi Mohammaditabar; Morteza Gholipour (Radiology Case Reports, 2025)
Elbow dislocation with fractures of the coronoid process and radial head, known as ``terrible triad injury'' (TTI), is a serious injury that is common in adults but rare in children. This report describes the case of a 9-year-old girl who experienced TTI after falling from a height of approximately 2 meters. She underwent closed reduction of the dislocation and had a K-wire inserted to stabilize her radial head, with removal after 3 weeks, followed by rehabilitation, resulting in satisfactory recovery of elbow joint motion at the 3-month follow-up. This case demonstrates that successful outcomes can be achieved through careful evaluation, appropriate imaging, and individualized treatment plans, while highlighting the need for prompt recognition and treatment to reduce complications like stiffness and arthritis in this rare pediatric injury pattern.